Developing Competitive Intelligence Capabilities Through Project Management Training: A Structural Model for Future Skills and Employability - Lei, An; Bamroongkhan, Pawatwong; Ponathong, Chakrit (Journal of Sustainable Competitive Intelligence, 2026)
Purpose: This study aims to develop and validate a Competitive Intelligence (CI)-oriented competency model by positioning project management (PM) training as a mechanism to enhance workforce intelligence capabilities, particularly in addressing the global skills mismatch crisis. Methodology/approach: The study adopts a mixed-methods design conducted in Shaanxi Province, China. Data were collected through interviews, surveys (n = 380), expert validation, and a quasi-experimental intervention (n = 30). The conceptual framework integrates Project Management, Social Cognitive Career Theory (SCCT), and Self-Determination Theory (SDT). Confirmatory Factor Analysis (CFA) was used to validate the measurement model. Originality/Relevance: This research introduces a novel CI-oriented competency model that conceptualizes leadership, innovation, and problem-solving as micro-foundations of intelligence capability. It uniquely links project management training with the development of strategic intelligence skills, addressing employability challenges in dynamic work environments. Key findings: The findings identify significant gaps in leadership, innovation, and problem-solving competencies, indicating deficiencies in intelligence readiness. Following a PM-based training intervention, substantial improvements were observed (Δ = 1.08–1.37; Cohen’s d = 1.931–2.456). Structural analysis confirms that these competencies significantly enhance employability by strengthening decision intelligence. Theoretical/methodological contributions: The study advances a human capital–driven CI capability framework by integrating PM, SCCT, and SDT. Methodologically, it demonstrates the effectiveness of combining CFA with quasi-experimental design to validate competency development models and provides a scalable approach for embedding intelligence-oriented training in higher education.